Ultrastructural features of platelets in the patients with diabetes mellitus type 2 in a decompensation with arterial hypertension under correction of arterial blood pressure with losartan. - Pertseva, N. O. (Морфологія / Morphologia / Morfologìâ, 2012)
We have conducted a quantitative evaluation of ultrastructural changes in the dynamics of platelets in the patients with diabetes mellitus type 2 in a decompensation phase with arterial hypertension under correction of arterial blood pressure with losartan and with considering of microalbuminuria. It is shown that in the patients with normalbuminuria observedsignificant degree violations of thrombocyte hemostasis, as a result of this is a significant increase in the relative amount of activated platelets with rising of content aggregated and degranulated forms and the appearance of numerous platelets with an imbalance of alpha and delta granules and reduction of the mitochondria.Inclusion of losartan in the treatment makes it possible to reduce the degree of ultrastructural disorders of platelets from the 6th month of the treatment. In the patients with microalbuminuria showed a strong damage of thrombocyte hemostasis due to significant growth in the content of the activated, degranulated and aggregated forms of platelets and development of hyperactivation ofplateletsbyhyalinetype. The standard treatment for one year is accompanied by increasing imbalance of granulomer of most platelets and the degree of the heteromorphic pool with a reliable higher content of degranulated and aggregated forms. Losartan usage limits the formation of giant spherical platelets with pseudopodia and since 6 month from starting treatment leads to significant reduction of hyperactivity and ultrastructural changes of platelet disorders.